UV photolysis of N2O isotopomers: Isotopic fractionations and product rotational quantum state Distributions - Daud, M.N. (2011)
The time-dependent quantum wave packet method is used to study the dynamics of the photodissociation processes for the isotopomers (NNO)-N-14-N-14-O-16, (NNO)-N-14-N-15-O-16, (NNO)-N-15-N-14-O-16, (NNO)-N-15-N-15-O-16, (NNO)-N-14-N-14-O-17 and (NNO)-N-14-N-14-O-18. In general, the computed isotopic fractionation factors derived from the absorption cross sections of five heavy isotopomers are in good agreement with the experimental results. Relative to the (NNO)-N-14-N-14-O-16 isotopomer, the N-2 rotational state distributions for the isotopically nitrogen substituted N2O are found to be entirely shifted to higher rotational states. Similar to its isotopic fractionation factors, the N-2 rotational state distributions for the asymmetric isotopomers (NNO)-N-14-N-15-O-16, (NNO)-N-15-N-14-O-16 are found to be observably different.